Analysis of Membranes Stretched Over a Unilateral Support - Binda, L.; Contro, R. (Engineering Transactions, 1981)
The main objective of the present. paper is to find the equilibrium configuration of membranes of various shapes, stretched over a plane frame, in the vicinity of a rigid, two-dimensional profile which supplies unilateral constraints to its deflections. The problem is considered under the following conditions: (i) the membrane is subjected to assigned, constant tension forces and to transversal loads; (ii) boundary conditions of the membrane are given by zero displacements along the contour of the frame; (iii) the deformations are small; (iv) the contact is frictionless and reactions are assumed to be vertical.